2021
DOI: 10.21833/ijaas.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transglutaminase on quality properties of fresh cheese

Abstract: Graph Microbial transglutaminase (MTGase) is an enzyme widely used in the food industry. In this study, MTGase had been applied to produce fresh cheese made from whole milk powder. To evaluate the impact of factors in reconstituted milk under the treatment of MTGase, a set of 18 experiments was conducted. Besides, a response surface methodology (a central composite design) was applied to evaluate the quality properties of fresh cheese according to the objective functions of hardness, yield, protein content, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, in a study of yogurt with added mTG similar to our research, the use of mTG did not affect Lactobacillus species but caused a decrease in the number of Streptococcus species (Ziarno and Zaręba, 2020). In addition, a study that found that the addition of mTG to fresh cheese reduced the number of Streptococcus thermophilus reported that the reason for this is the cross-linking of peptides required for the growth of Streptococcus due to enzyme activity, and therefore may affect the growth of this strain (Pham et al, 2021).…”
Section: Microbiological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a study of yogurt with added mTG similar to our research, the use of mTG did not affect Lactobacillus species but caused a decrease in the number of Streptococcus species (Ziarno and Zaręba, 2020). In addition, a study that found that the addition of mTG to fresh cheese reduced the number of Streptococcus thermophilus reported that the reason for this is the cross-linking of peptides required for the growth of Streptococcus due to enzyme activity, and therefore may affect the growth of this strain (Pham et al, 2021).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…The samples added with mTG were rated better than the whey cheese without mTG. This is likely due to the fact that the mTG enzyme brings small proteins together through the cross-linking effect, resulting in more uniform and smaller gaps in the structure (Pham et al, 2021). This effect resulted in a smoother and straighter appearance of the cheese.…”
Section: Sensory Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using capillary gel electrophoresis, and demonstrated the changes in the j-CN and other caseins and molecular weight changes due to TGase crosslinking. TGase has been used in various dairy products such as yoghurt (Jaros et al 2007;Guyot and Kulozik 2011), fresh cheese (Pham et al 2021), Mozzarella cheese analogues (Hebishy et al 2022) or imitation Mozzarella cheese , and PCP , which resulted in significant modifications in functional and structural properties reported in these products. reported changes in functionality due to TGase action in MCC and MPC and novel dairy protein ingredients can be produced using TGase (Raak and Corredig 2022;.…”
Section: Introductionmentioning
confidence: 99%
“…2007; Guyot and Kulozik 2011), fresh cheese (Pham et al . 2021), Mozzarella cheese analogues (Hebishy et al . 2022) or imitation Mozzarella cheese (Salunke et al .…”
Section: Introductionmentioning
confidence: 99%